Congenital factor X deficiency: a case of unexplained neonatal anemia presenting with intracranial hemorrhage and hemorrhagic meningitis in the first month of life in a resource-limited setting - Lourembam, Radhapyari; T., Arularasu; Moirangthem, Amarjit; C., Shyamsunder Singh (International Journal of Contemporary Pediatrics, 2025)
Factor X (FX) deficiency is an exceptionally rare inherited autosomal recessive coagulation factor disorder, posing significant challenges due to its rarity and lack of evidence-based management guidelines. It can manifest in a spectrum of hemorrhagic symptoms, including life-threatening intracranial hemorrhages. Here, we reported a case of congenital FX deficiency who presented with intracranial hemorrhage (ICH), complicated by hemorrhagic meningitis within the first month of life, following unexplained neonatal anemia. Early diagnosis and prompt intervention are crucial, especially in resource-limited settings, for managing this rare condition. This case underscores the difficulties encountered in managing rare conditions like FX deficiency and emphasizes the necessity for further research and collaboration to establish standardized management protocols. By adding to the limited literature on Factor X deficiency, this case report emphasizes considering FX deficiency in severe neonatal anemia and highlights the importance of personalized patient care in addressing rare diseases.